Financial Assessment of Public and Private Banks in India - Johri, Swaricha; Singh, Manjeet (International Journal of Social Sciences and Management, 2015)
The banking sector is the backbone of the economy and plays an important financial intermediary role, their health is very critical to the health of the general economy at large. In order to ensure a healthy, solid and stable banking sector, the banks must be analyzed and evaluated in a way that will allow the smooth correction and removal of the potential vulnerabilities. The present study is done with the objective to analyze the financial performance of the commercial banks in India. CAMEL Approach is applied to evaluate the financial performance of SBI and ICICI bank. Based on the set of indicators as defined by CAMEL framework the financial performance is being evaluated with the help of various ratios. Comparison of financial performance was done by applying Independent sample t- test. The study concluded that ICICI bank is more efficient in terms of capital adequacy and can resists risk more effectively that SBI. The financial statements of SBI & ICICI bank from the period of 2009-10 to 2013-14 have been analyzed for the purpose of the study. Whereas SBI's earning capabilities are far better than ICICI. More or less both banks are carrying on their operations effectively. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 228-235 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12417